Bioerosional marks in the shells of two sea turtle taxa from the middle Eocene of Belgium - Andrea Guerrero; Thierry Smith; Adán Pérez-García (Fossil Record)
This study analyses the diverse types of bioerosion marks on the shells of two sea turtle specimens from the Lutetian (middle Eocene) of Belgium. The objective is to understand the physical stressors affecting these organisms in ancient marine environments and to identify the potential factors responsible for these changes. The first specimen, the holotype of Eochelone brabantica, presents multiple erosive anomalies on its costal plates. The second individual, corresponding to Puppigerus camperi, exhibits different types of shell deviations, also of an erosive character. The combination of macroscopic and imaging techniques (i.e., CT scanning and 3D surface scanning) allow us the precise observation and identification of the different alterations. Comparative analyses suggest several external factors as potential causes of the anomalies of the two specimens (i.e., invertebrate feeding traces and trauma). This detailed examination provides specific insights into the types and causes of shell alterations in these Eocene turtles, offering a clearer understanding of their interactions in the marine ecosystem in which they lived.